Applied Use of Doppler Ultrasonography in Bovine Reproduction - Fontes, Pedro L. P.; Oosthuizen, Nicola (Frontiers in Animal Science, 2022)
The use of Doppler ultrasonography to quantify blood vascularization in reproductive organs has increased over the past decade. Doppler technology has predominantly been explored in research settings to evaluate uterine blood flow and to assess follicular and luteal blood perfusion. Recent research has also explored the use of Doppler technology in applied reproductive management for both the beef and dairy industries and has focused on the use of luteal color Doppler ultrasonography to evaluate embryo transfer recipients and perform early pregnancy diagnosis. Although significant progress has been made in the use of Doppler ultrasonography, uptake of this technology is still currently limited in the cattle industry. This review summarizes the recent developments in the applied use of color Doppler ultrasonography for reproductive management in beef cattle herds.